2006
DOI: 10.1002/jsfa.2424
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Weibull model to describe inactivation of Listeria monocytogenes and Escherichia coli by citric and lactic acid at different temperatures

Abstract: Inactivation of Listeria monocytogenes and Escherichia coli by citric (10-150 g L −1 ) and lactic (1-60 mL L −1 ) acids at different temperatures (4, 20, 40 • C) has been investigated. Bactericidal effect of both acids was dependent on time and temperature of exposure and acid concentration. Survival curves of L. monocytogenes treated by lactic acid were concave downward and those treated by citric acid were linear. On the other hand, survival curves of E. coli treated by both organic acids were concave upward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 17 publications
2
24
0
Order By: Relevance
“…We propose a mathematical model describing microbial inactivation after ALA-based photosensitization. Various functions could be applied for approximation of such inactivation curves [12][13][14][15]. Meanwhile, most of them consist of too many parameters, which cannot be described in time dimension.…”
Section: Resultsmentioning
confidence: 99%
“…We propose a mathematical model describing microbial inactivation after ALA-based photosensitization. Various functions could be applied for approximation of such inactivation curves [12][13][14][15]. Meanwhile, most of them consist of too many parameters, which cannot be described in time dimension.…”
Section: Resultsmentioning
confidence: 99%
“…A downward concavity (p > 1) was observed for E. coli at 10-40 W and for L. innocua at 10 and 20 W. An upward concavity (p b 1) was found for L. innocua at 40 W. An upward concavity implies that the remaining cells are able to adapt to the applied stress and downward concavity implies that the remaining cells became increasingly damaged (van Boekel, 2002). The scale parameter from the Weibull model has a probabilistic interpretation and represents the time of the first decimal reduction (Virto, Sanz, Alvarez, Condon, & Raso, 2006). With increasing plasma operating power the scale parameter of E. coli decreased whereas the scale parameter of L. innocua was highest at 20 W and lowest at 40 W. However, the scale parameter of the tested bacteria indicated that L. innocua is more resistant against atmospheric pressure plasma than E. coli.…”
Section: Modeling Of Inactivation Kineticsmentioning
confidence: 90%
“…After the first 30 to 60 min, survival behavior was concave (up) or nearly log linear. As in previous studies (9,19,25,41), a Weibull model was used to describe the survival curves. E. coli O157:H7 exposed to 4% NaCl and less than 20 mM acetic acid had survival curves with a remarkable tailing behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to quantify the effects of antimicrobials used in preventing the survival of O157:H7 in acidified vegetable products. Mathematical models of microbial inactivation of bacteria by heat, pressure, and chemicals have been extensively studied (1,9,15,16,19,41). Traditional approaches to measuring the killing of bacteria by environmental stress use first-order kinetics (16).…”
mentioning
confidence: 99%